Extraction and characterization of microplastics in soil: A case study from the Hetao Irrigation District - Ho, Chia Min; Feng, Weiying; Deng, Yuxin; Li, Xiaofeng; Ngien, S. K. (MDPI, 2025)
Microplastics (MPs) pollution has become a global environmental issue. Soil, as a key environmental medium, serves as an important sink and carrier of MPs. Accurate and efficient extraction of MPs from soil matrices is essential for understanding their distribution, composition, and environmental behavior. This study presents a refined extraction method that combines two-step density separation with sodium chloride (NaCl, 1.20 g/cm3), hydrogen peroxide (H2O2) digestion for organic matter removal and a Fractionated Filtration Method (FFM) to capture MPs across multiple particle size ranges. Polymer identification and size characterization were performed using the high-throughput Agilent 8700 Laser Direct Infrared (LDIR) imaging system. Method validation demonstrated a recovery rate of 85% based on 100 μm MPs standards spiked into soil and minimal background contamination of 5–8 particles in blank controls, confirming the reliability of the workflow. Applying this method to agricultural soils from the Hetao Irrigation District revealed widespread MP contamination, with concentrations ranging from 5778 to 31,489 particles/kg and an average of 16,461 ± 8097 particles/kg. More than 99% of MPs were smaller than 500 μm, with the 10–30 μm fraction dominating the distribution. Polypropylene (PP), polyamide (PA), and polyethylene (PE) accounted for over 90% of detected MPs. This refined method enables reproducible extraction and accurate characterization of fine MPs in complex soil environments and provides a practical foundation for advancing standardized soil MP monitoring protocols.